The Nature of Mobile Work and the Needs for Mobile Work Technology Support: A Task-Technology Fit Perspective - Zheng, Wuping (My University, 2007)
The rapid growth in the use of wireless communication and portable devices in recent years has created a great potential for a variety of mobile work technology support. However, we still lack the theories to explore the nature of mobile work, examine the needs for mobile work support, and identify the appropriate mobile technologies for various kinds of mobile work. This study is an attempt to meet the challenge. A mobile task model is proposed in this study which includes four dimensions: task complexity, task interdependence, time criticality, and location sensitivity. New instruments are developed to measure the constructs of time criticality and location sensitivity. Six typical mobile work support functions are examined: mobile communication, mobile information searching, mobile transaction processing, location related service, mobile job dispatching and mobile office. In light of contingency theory and attitude/behavioral theory, a research model is proposed to identify the ideal fit between task characteristics and typical mobile work support functions. Based on empirical data from real mobile workers, the nature of mobile work and the differences in mobile work between mobile knowledge workers and field workers are analysed. New instruments for the time and location related constructs are validated through the empirical data. The differences in perceived usefulness of the typical mobile work support functions between mobile knowledge workers and field workers are presented, as well as those of the current usage and intention to use. Finally, the ideal fit is identified on the basis of the empirical data. This study contributes both to theory and practice. The establishment of a mobile task model, including the development of new instruments for time and location constructs, provides a foundation for future mobile business research. The identification of the ideal fit between task characteristics and mobile technology functions, based on contingency theory and attitude/behavioral theory, extends and enriches mobile business research. The results of the study can provide guidance and recommendations on how to strategically plan and implement suitable mobile applications, and to identify opportunities for the development of appropriate technological solutions for mobile work support.
Keywords: mobile work; technology support